1996
DOI: 10.1108/09596119610152069
|View full text |Cite
|
Sign up to set email alerts
|

Hospitality operations: patterns in management, service improvement and business performance

Abstract: Provides an overview of developments in hospitality operations management as reflected by articles published in: International Journal of Contemporary Hospitality Management, International Journal of Hospitality Management, International Journal of Service Industry Management and Service Industries Journal during 1995 (business performance, customers and service improvement, operations and the curriculum, strategy and development) and during the six‐year period 1989‐1994 (structural relationships in hospitalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…The authors accordingly suggested service quality and subdimensions of SERVQUAL as performance attributes from a consumer’s standpoint. In the similar vein, Teare [ 26 ] explained that performance in the consumer’s point of view indicated customer orientation, process evaluation and improvement, service quality, and service performance in hospitality operations. In light of technology adoption, Dabholkar [ 21 ] proposed an attribute-based model that focused on SST attributes with service quality.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The authors accordingly suggested service quality and subdimensions of SERVQUAL as performance attributes from a consumer’s standpoint. In the similar vein, Teare [ 26 ] explained that performance in the consumer’s point of view indicated customer orientation, process evaluation and improvement, service quality, and service performance in hospitality operations. In light of technology adoption, Dabholkar [ 21 ] proposed an attribute-based model that focused on SST attributes with service quality.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Hospitality and Tourism General Review Dann et al (1988) ATR, JLR 1974-1986 Subject matter, Nature of research, Statistical technique Chon et al (1989) CHRQ, HERJ, IJHM, FIU 1967-1986 Author type, Nature of research, Subject matter Reid & Andereck (1989) ATR, JTR, TM 1978-1987 Tourism attractions Blum (1996) HRJ 1989 Organizational trends Hu (1996) JTTM 1992 Tourism marketing Eccles & Costa (1996) ATR, TM, TTA 1989 Tourism development Prabhu (1996) CHRQ 1990 Challenges for hospitality operators Teare (1996) IJCHM, IJHM, IJSIM, SIJ 1989 Hospitality operating patterns Bowen (1996) FIU 1989 Hospitality environmental changes Crouch & Ritchie (1998) NA 1976-1997 Meeting site-selection process Carlsen (1999) NA 1988-1998 Meeting management Pandit & Parks (2000) HRJ, CHRQ, JTR 1970-1997 Lodging marketing former focuses on identifying general trends of methodological use and research areas over the years studied. Studies in this category usually provide specific numbers (frequencies and percentages) in the crosstabulation analysis format, comparing research and statistical orientations of each participating journal based on those numbers.…”
Section: Research Focusmentioning
confidence: 99%
“…The emerging trend of using the thematic approach in hospitality and tourism review was well illustrated by the fact that the International Journal of Contemporary Hospitality Management (1996) devoted an issue to the themes of hospitality and tourism field (Baloglu & Assante, 1999). Studies in that issue content-analyzed hospitality and tourism articles published in each target journal and provided trends and themes on specific hospitality and tourism areas, including organizational trend of hospitality industry (Blum, 1996), travel and tourism marketing (Hu, 1996), tourism development (Eccles & Costa, 1996), challenges for hospitality operators (Prabhu, 1996), patterns of hospitality operations (Teare, 1996), and managing environmental change (Bowen, 1996).…”
Section: Myong Jae Lee and Ki-joon Backmentioning
confidence: 99%
“…Literature from the UK has concentrated on the strategic operational developments and service development issues connected with multi-site management (Teare, 1995(Teare, , 1996. There are a number of articles covering the operational systems aspects of the contemporary industry (Jones and Lockwood, 1995;Kirk, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%